2019
DOI: 10.1101/671933
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dissociating activation and integration of discourse referents: evidence from ERPs and oscillations

Abstract: A key challenge in understanding stories and conversations is the comprehension of 'anaphora', words that refer back to previously mentioned words or concepts ('antecedents').In psycholinguistic theories, anaphor comprehension involves the initial activation of the antecedent and its subsequent integration into the unfolding representation of the narrated event.A recent proposal suggests that these processes draw upon the brain's recognition memory and language networks, respectively, and may be dissociable in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(15 citation statements)
references
References 159 publications
(238 reference statements)
1
13
1
Order By: Relevance
“…One study with a similar manipulation did not report any LPC modulation (Yang et al, 2007). And while one recent study with repeated proper name anaphors also reported enhanced LPC for new names (Coopmans and Nieuwland, 2019), two other studies with proper names reported a reverse LPC pattern (Van Petten et al, 1991; Swaab et al, 2004). For example, in a study on natural text comprehension, Van Petten et al (1991) reported enhanced LPC amplitude for repeated proper names compared to novel names, and suggested that these effects reflect the retrieval of semantic information associated with known names 2 .…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…One study with a similar manipulation did not report any LPC modulation (Yang et al, 2007). And while one recent study with repeated proper name anaphors also reported enhanced LPC for new names (Coopmans and Nieuwland, 2019), two other studies with proper names reported a reverse LPC pattern (Van Petten et al, 1991; Swaab et al, 2004). For example, in a study on natural text comprehension, Van Petten et al (1991) reported enhanced LPC amplitude for repeated proper names compared to novel names, and suggested that these effects reflect the retrieval of semantic information associated with known names 2 .…”
Section: Introductionmentioning
confidence: 95%
“…In a recent study on comprehension of proper name anaphors, Coopmans and Nieuwland (2019) observed effects in both the theta and gamma frequency range. Their participants read story contexts that described characteristics of two people (e.g., “John and Peter are the best players in the football team”), followed by a target sentence containing a repeated or novel proper name that was either congruent or incongruent with the discourse context (e.g., “The top scorer of the team was John with thirty goals in total”).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations